Diseño y construcción de un banco de pruebas para pinzas amperimétricas (2020)
The objective of this project is the design and construction of a test bench for current clamps for the testing and calibration laboratory of Empresa de Energía de Boyacá S.A. E.S.P. (EBSA). This test will evaluate the absolute error of the current clamps owned by the company. Where the value read by the device is compared with the calculation value. The main components of the test bench are a cabinet, a Variac or variable transformer, a voltage transformer (gearbox), two current coils and measuring devices (digital voltmeter and ammeter). Through the Variac, voltage is injected to the voltage transformer and this will inject current to the coils, which by transformation ratio will increase the input current in a ratio of 1 to 109. This means that for each ampere that is injected to the current coil it increases it to 109 amps, up to a maximum range of 600 amps. Test were carried out with various types of clamps and in a different input current range and the results obtained were analyzed, which shows us that the bench complies with parameters required by the international standard (SIT/Tec-014/06 (Revision 0 of 2006-04-03). Making this project will allow us extend the scope of the laboratory with the purpose of characterize the quality of measuring amperes clamps own of EBSA